Pengolahan Sampah Plastik Menjadi Polybag Melalui Program KKN Di Kelurahan Bungus Barat - Rahim, Bulkia; Pratama, Ayu Zulmi Amanda; Septriani, Tesa; Kahfi, Fadlan Muhammad; Armensyah, Rafi; Mushil, Novando (Universitas Dehasen Bengkulu, 2023)
In RW 03 Bungus Barat, with the increasing population and increasing use of plastic waste by the community, the amount of plastic waste generated by the community is increasing day by day. The increasing generation of plastic waste causes accumulation of waste and has many negative impacts. To overcome this negative impact, Padang State University Community Service students conducted counseling and workshops on processing plastic waste into polybags which are expected to bring economic value. We invite the community in RW 03 Bungus Barat and students to take advantage of plastic waste and be creative in processing it into polybags. The target of this counseling and workshop is the public and students who do not know how to process recycled plastic waste. This activity was carried out in such a way and with the aim of obtaining the results obtained by the community in RW 03 Bungus Barat and students who have knowledge about organic waste and non-organic waste to produce handicrafts with economic value.